Novel RPTPγ and RPTPζ splice variants from mixed neuron–astrocyte hippocampal cultures as well as from the hippocampi of newborn and adult mice - Taki, Sara; Boron, Walter F.; Moss, Fraser J. (Frontiers in Physiology, 2024)
Receptor protein tyrosine phosphatases γ and ζ (RPTPγ and RPTPζ) are transmembrane signaling proteins with extracellular carbonic-anhydrase-like domains that play vital roles in the development and function of the central nervous system (CNS), and are implicated in tumor suppression, neurodegeneration, and sensing of extracellular [CO2] and [HCO3 -]. RPTPγ expresses throughout the body, whereas RPTPζ preferentially expresses in CNS. Here, we investigate differential RPTPγ-RPTPζ expression in three sources derived from a wild-type laboratory strain of C57BL/6 mice: (a) mixed neuron-astrocyte hippocampal (HC) cultures 14 days, post-isolation from P0-P2 pups; (b) P0-P2 pup HC; and (c) 9--12 week-old adult HC. Regarding RPTPγ, we detect the Ptprg variant-1 (V1) transcript, representing canonical exons 1-30. Moreover, we newly validate hypothetical assembly[XM_006517956] (propose name, Ptprg-V3), which lacks exon 14. Both transcripts are in all three HC sources. Regarding RPTPζ, we confirm expression of Ptprz1-V1, detecting it in pups and adults, but not cultures; and Ptprz1-V3 through -V7 in all three preparations. We newly validate hypothetical assemblies Ptprz1-X1 (in cultures, pups), -X2 (all 3), and -X5 (pups, adults), and propose to re-designate them as Ptprz1-V0, -V2, -V8, respectively. The diversity of RPTPγ and RPTPζ splice variants likely corresponds to distinct signaling functions, in different cellular compartments, during development vs. later life. In contrast to previous studies that report divergent RPTPγ and RPTPζ protein expression in neurons and sometimes glia, we observe that RPTPγ and RPTPζ co-express in the somata and processes of almost all HC neurons, but not astrocytes, in all three HC preparations.